Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1365-2699.2006.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Are islands more susceptible to plant invasion than continents? A test using Oxalis pes‐caprae L. in the western Mediterranean

Abstract: Aim We tested the relative vulnerability of islands to Oxalis pes-caprae L. invasion compared to mainland regions. Oxalis pes-caprae is a South African annual geophyte that reproduces via bulbils, and has spread in many Mediterranean and temperate regions of the world where introduced. Our study is one of the first detailed regional analyses of the occurrence and local abundance of a non-native plant.Methods We conducted an extensive survey (2000 sampling points) to examine local and coarse-scale patterns in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 19 publications
3
51
0
1
Order By: Relevance
“…Island ecosystems are particularly susceptible to plant invasions (Gimeno et al, 2006). In Hawaii, it is estimated that o10% of the original tropical dry forest remains (Bruegmann, 1996), primarily as a result of the introduction of invasive species and changes in disturbance regimes (Hughes et al, 1991;D'Antonio & Vitousek, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Island ecosystems are particularly susceptible to plant invasions (Gimeno et al, 2006). In Hawaii, it is estimated that o10% of the original tropical dry forest remains (Bruegmann, 1996), primarily as a result of the introduction of invasive species and changes in disturbance regimes (Hughes et al, 1991;D'Antonio & Vitousek, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Islands can be more exposed to invasions because of small sizes compared to mainland, which facilitates colonization by invasives, once these have reached the island system (Gimeno et al 2006).…”
Section: Ecological Invasivenessmentioning
confidence: 99%
“…approximately 10% of the World's vascular flora: thrive there. The highest levels of endemism have been recorded on islands (Heywood, 2011), where the ecological threat posed by alien invasive species seems to be higher than in adjacent mainland areas (Gimeno & al., 2006;Hulme & al., 2007). It has been suggested that island biota appear more vulnerable to invasions due to the presence of empty niches in unsaturated communities, the absence of key functional groups, and a generally lower competitive ability of the native species (Hulme, 2004).…”
Section: Plant Invasion Within the Mediterraneanmentioning
confidence: 99%
“…Among natural habitats, wetlands and coastal areas are relatively richer in IAS than other habitats, suggesting that those habitats may suffer a greater impact (Chytrý & al., 2009;Arianoutsou & al., 2010). In contrast, Mediterranean mature and stable woodlands, dominated by evergreen shrubs and trees, seem to be quite resistant to invasion (Affre & al., 2010;Arianoutsou & al., 2010;), although human disturbance, such as wildfires or silvicultural interventions, may alter canopy structure and so understory light availability, thus allowing the establishment of heliophilous tree species (Constán-Nava & al., 2010;Badalamenti & al., 2012); invasions by such species have already caused a reduction in species richness and a significant alteration of functioning of Mediterranean ecosystems (Vilà & al., 2006;Traveset & al., 2008). However, the major ecological impacts caused by IAS have probably yet to be realized, because a worsening of the current situation is expected, both in terms of number and spread, and consequently of their likely damaging effects.…”
Section: Plant Invasion Within the Mediterraneanmentioning
confidence: 99%